2020
DOI: 10.1002/app.50246
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study for the behavior of 3D‐printed and compression molded PLA/POSS nanocomposites

Abstract: Because of the biocompatible and nontoxic character of both PLA (polylactide) and POSS (Polyhedral Oligomeric Silsesquioxane) nanoparticles, recently being a significant alternative for biomedical parts; the main purpose of this study was to investigate performance of the 3D‐printed PLA/POSS nanocomposites with respect to the compression molded PLA/POSS specimens. Due to the higher uniformity and higher homogeneity in the distribution of POSS nanoparticles in each PLA matrix layer, mechanical tests (tensile, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The 10% PBS/PLA blend had the greatest Xc value of 7.4%. The glass transition temperature (Tg), shown in Table 3, shows that the Tg of neat PLA was 63.8 °C, which was very close to the values of 65.0 °C reported by Marie-Joo et al [ The glass transition temperature (T g ), shown in Table 3, shows that the T g of neat PLA was 63.8 • C, which was very close to the values of 65.0 • C reported by Marie-Joo et al [1] and 60.9 • C reported by Yelda et al [45], and the observation of T g changing for the blends showed that the glass transition temperatures of PLA would be reduced slightly with the increase of PBS content in the blend. For example, T g for the blend [PBS/PLA] = [10/90] was 62.9 • C, and for the blend [PBS/PLA] = [20/80], T g reduced to 61.7 • C, which were 0.9 • C and 2.1 • C lower than that of pure PLA, respectively.…”
Section: Melt and Crystallization Behaviorsupporting
confidence: 87%
“…The 10% PBS/PLA blend had the greatest Xc value of 7.4%. The glass transition temperature (Tg), shown in Table 3, shows that the Tg of neat PLA was 63.8 °C, which was very close to the values of 65.0 °C reported by Marie-Joo et al [ The glass transition temperature (T g ), shown in Table 3, shows that the T g of neat PLA was 63.8 • C, which was very close to the values of 65.0 • C reported by Marie-Joo et al [1] and 60.9 • C reported by Yelda et al [45], and the observation of T g changing for the blends showed that the glass transition temperatures of PLA would be reduced slightly with the increase of PBS content in the blend. For example, T g for the blend [PBS/PLA] = [10/90] was 62.9 • C, and for the blend [PBS/PLA] = [20/80], T g reduced to 61.7 • C, which were 0.9 • C and 2.1 • C lower than that of pure PLA, respectively.…”
Section: Melt and Crystallization Behaviorsupporting
confidence: 87%
“…Compression molding is a melt processing method for fabricating polymer films (typically with over hundreds of micrometer thickness), often without the use of solvent. [142][143][144] In this process, a filler-containing polymer composite is heated at an elevated temperature within a mold and then compressed under high pressure, followed by cooling down to room temperature. [145][146][147] The high pressure applied during this compression process not only shapes/molds the polymer composite but also orients the embedded fillers with their basal plane parallel to the film surface.…”
Section: Compression Moldingmentioning
confidence: 99%
“…Polyhedral oligomeric silsesquioxane (POSS), another biocompatible and non-toxic polymer nanoparticle, also increases the flexural strength (22%), flexural modulus (9%), and fracture toughness (117%) of 3D-printed PLA/POSS nanocomposites compared to neat PLA [ 90 ]. PLA/POSS nanocomposites were formed through melt-mixing of pre-dried samples and then extrusion and FDM 3D printing, resulting in a good distribution of nanoparticles in the PLA matrix.…”
Section: Other Additivesmentioning
confidence: 99%
“…PLA/POSS nanocomposites were formed through melt-mixing of pre-dried samples and then extrusion and FDM 3D printing, resulting in a good distribution of nanoparticles in the PLA matrix. Importantly, the addition of POSS allowed the samples to remain in a phosphate buffered saline solution at 37 °C for 120 days with little mechanical or physical deterioration, suggesting their potential use for longer-term medical implants [ 90 ].…”
Section: Other Additivesmentioning
confidence: 99%